Peran Komunitas Barisan Bengkak Bersholawat (BRINGAS) Sebagai Media Dakwah dalam Meningkatkan Religiusitas Masyarakat di Desa Bengkak Wongsorejo Banyuwangi - Hanifah, Ayunda Nur; Shodiqi, Nadia Zahra; Nurmely, Nurmely; Nikmah, Maghfirotun; Bramayudha, Airlangga (Hikmah, 2024)
The purpose of this research is to investigate the significance of the BRINGAS community ‘’Barisan Bengkak Bersholawat’’ as a medium of da’wah in increasing community religiosity in Bengkak Village, Wongsorejo, Banyuwangi. The study approach used was descriptive qualitative, comprising in-depth interviews with members of the Bringas community, participatory observation, and documentation. The findings revealed that the BRINGAS community plays an important role in enabling and increasing community religiosity through a variety of religious activities such as pengajian, sholawat, and other religion-based social events. The active participation of the community in activities initiated by the BRINGAS community has shown an increase in community behavior, especially in terms of religiosity. This study concludes that da'wah communities such as BRINGAS can be agents of change in improving community religiosity. This research suggests that the da'wah model applied by BRINGAS can be taken and replicated by other da'wah communities in order to achieve similar goals.